Comparative analysis of biopolymer films derived from corn and potato starch with insights into morphological, structural and thermal properties - N. Pooja; Soumyabrata Banik; Ishita Chakraborty; H. C. Sudeeksha; Sib Sankar Mal; Pornsak Srisungsitthisunti; Ajeetkumar Patil; Krishna Kishore Mahato; Nirmal Mazumder (Discover Sustainability, 2024)
Abstract Starch biopolymer films were prepared using the solvent casting method involving acetic acid hydrolysis and glycerol plasticization. This process facilitated a more uniform distribution of plasticizers within the starch matrix, enhancing the films' flexibility. Fourier-transform infrared (FTIR) and Raman spectroscopy confirmed the formation of ester linkages and structural changes in the biopolymer films, attributed to glycerol integration. The optimal formulation comprised 6% starch, 6.8% acetic acid, and 6.8% glycerol. X-ray diffraction (XRD) analysis revealed a reduction in crystallinity of the starch during film formation, enhancing flexibility. Second harmonic generation (SHG) and coherent anti-Stokes Raman scattering (CARS) microscopy indicated that potato starch films had higher crystallinity compared to corn starch films. Thermal analysis via differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) showed that potato starch films exhibited lower gelatinization temperatures and higher thermal stability compared to corn starch films. Functional characterization demonstrated that higher starch content decreased water solubility and water vapor transmission rate, while increasing starch content improved the film's structural integrity. The films were hydrophilic, with static water contact angles indicating moderate wettability. Degradation studies showed that the films were stable in neutral and basic conditions but degraded under acidic conditions over time. The results suggest that potato starch films, with optimized glycerol and acetic acid content, offer improved flexibility, thermal stability, and structural integrity compared to corn starch films. Their performance in various conditions highlights their potential for specific applications, particularly where moisture and environmental stability are critical.